33 The therapeutic benefit of upgrade to cardiac resynchronization therapy in patients with pacing induced cardiomyopathy. (6th October 2022) - Kerley, R; O'Dowling, C; Campos, F; Murphy, R; Walsh, K; Fahy, G
Abstract : Background: Pacing induced cardiomyopathy (PICM) is an important cause of heart failure in patients with a right ventricle (RV) pacing burden. Recent evidence suggests upgrade to cardiac resynchronization therapy (CRT) may reverse PICM. Objective: To assess the extent and identify predictors of improvement following upgrade to CRT in patients with PICM. Methods: We retrospectively analysed 43 patients undergoing CRT upgrade for PICM over a ten-year period 2011–2021 at our tertiary referral centre. All patients who underwent device upgrade from a dual or single chamber ventricular pacemaker to CRT were included. PICM was defined as a decrease of ≥10% in left ventricular ejection fraction (LVEF), resulting in LVEF <50% among patients experiencing ≥ 20% RV pacing without an alternative cause for cardiomyopathy. Results: LVEF significantly improved from 28.7% pre-upgrade to 44.3% post CRT upgrade (p < 0.01). Most LVEF Improvement occurred within the first 3 months with a mean LVEF improving from 28.7% to 41.5%. Of 37 patients with severe LV dysfunction, 34 (91.9%) improved to a LVEF >35% with a median time of 9.4 months and 13 patients (35.1%) improved to a LVEF > 50% with a median time of 14.0 months ( table 1 ). The LV end diastolic diameter improved from 5.9 cm pre-upgrade to 5.4 cm post upgrade which was statistically significant (p < 0.01). In linear regression, ACE inhibitor or ARB use was associated with significant LVEF improvement (+7.21%, p = 0.05). We observed a low rate of complications and one in four CRT upgrades required venoplasty (10/43, 23.3%). Conclusion: We provide definitive evidence for the therapeutic role of CRT upgrade in the management of patients with PICM. Our data shows that 91.4% of patients with severe PICM will see recovery of the LV function to an EF >35%.